2018
DOI: 10.1007/s00701-018-3564-2
|View full text |Cite
|
Sign up to set email alerts
|

Mastoid foramen, mastoid emissary vein and clinical implications in neurosurgery

Abstract: Despite excellent knowledge of anatomy, however, good pre-operative examination using imaging methods and mastering of microsurgical techniques create the base for successful treatment of pathological structures in these anatomically complex areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In the present study, points A, B and C could be easily identified during craniotomy [3,8,20,24]. However, the most important part of this study was that we utilized a reference point, the TMN, to improve the accuracy of localization.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present study, points A, B and C could be easily identified during craniotomy [3,8,20,24]. However, the most important part of this study was that we utilized a reference point, the TMN, to improve the accuracy of localization.…”
Section: Discussionmentioning
confidence: 93%
“…The anterosuperior and inferomedial points of the transverse-sigmoid sinus junction (ASTS and IMTS) represent the most posterior edge of the middle fossa and the most superolateral limit of the retrosigmoid approach, respectively. Accurately locating these key points on the external surface of the cranium is important in lateral skull base craniectomy [1][2][3][4]. Traditionally the squamosal-parietomastoid suture junction (SP) and asterion have been regarded as the classic landmarks for assisting with identifying the ASTS and IMTS, respectively [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the emissary veins may represent a primary outflow route in patients with intracranial hypertension, high flow vascular malformation, obstruction in the internal jugular veins, or hypoplasia/aplasia. 3,12,13 The emissary veins prevent increases in intracranial pressure by providing cerebral venous drainage in patients with pathologies of the neck or base of the skull or with internal jugular vein occlusion. [15][16][17] Calibration of the emissary vein canals can increase under conditions of high vascular pressure or hypoplasia or aplasia of the jugular vein that may accompany states such as craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that there may be more than one MEC/MEV with differing diameters. 3,12,13,19 However, MEVs or MECs have not been investigated in patients with otitis. Our review of the literature revealed one previous study assessing the petrosquamosal sinus (PSS), a rare emissary vein, using HRCT in patients with otitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation